Mitigation of Oxidized Oil Effects on Production Performances and Meat Quality of Broilers by Dietary Supplementation of Allicin - Arabela Elena Untea; Petru Alexandru Vlaicu; Iulia Varzaru; Alexandra Gabriela Oancea; Mihaela Saracila (Life)
The objective of this study was to evaluate the effects of dietary oxidized oil and allicin (two different dietary sources) as natural antioxidants on the growth performance and meat quality of broilers. A total of 200 one-day-old Ross 308 broilers were randomly divided into four dietary groups (50 birds/group). The experimental groups (OO—oxidized oil; OOA—oxidized oil and allicin; OOG—oxidized oil and garlic leaves) differed from the control one by the presence of oxidized oil in their dietary structure (peroxide value 9.07 (OO, OOA and OOG groups) vs. 1.70 (C group) meq active oxygen/kg). The diets given to the experimental groups differed from each other by the presence of allicin (100 mg/kg inclusion rate as extract (OOA) and 0.5% as garlic leaf powder (OOG)). At the end of the experiment, six animals/group were slaughtered, meat samples (breast and thigh) were collected, and nutritional value was established. The results showed that the allicin included in the experimental diet did not influence the proximate composition of breast meat (crude protein, fat, ash, and dry matter). The fatty acid profile was determined for each group of samples; a significant decrease in omega 3 FAs was noticed between the C group and the E groups (3.27% vs. 1.46%, 1.60%, and 1.56%) in breast meat samples, and a corresponding increase was noticed in saturated fatty acid (SFA) concentrations. Health indices with implications for atheroma and thrombus formation and cholesterol level were negatively affected by the presence of oxidized oil in the experimental diets, but the allicin extract supplement appeared to mitigate its influence. A positive influence of the dietary supplement was noticed on antioxidant capacity and polyphenol concentrations determined in breast and thigh samples under allicin supplement influence. The results of the current study revealed that the use of low oxidized oil in broilers diets did not affect productive performance. The nutritional quality of meat (breast and thigh) was negatively influenced by the presence of oxidized oil, but allicin supplements (extract or garlic leaves) improved lipid quality indices and antioxidant potential.